ANALISIS PENERAPAN PRINSIP TRANSPARANSI DAN AKUNTABILITAS DALAM PENGELOLAAN KEUANGAN SEKRETARIAT DPRD PROVINSI JAWA TIMUR - Siregar, Natasya Tiony Aectha (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to determine the implementation of transparency and accountability in the financial management of the Secretariat of the East Java Provincial DPRD. The research method used in this study is qualitative with a descriptive approach. The type of data used is primary data obtained through interviews, observations, and documentation. The results of the study indicate that the implementation of transparency at the Secretariat of the East Java Provincial DPRD has been implemented well, although there are still several stages that need to be improved. The implementation of accountability has also been implemented well, although there are still several stages that need to be improved